RETRACTED: The constitutional right to a favorable environment as the basis for the ecologization of modern Russian legislation - Kostenko M.; Lupandina O.; Dymnikova O.; Finochenko V.; Dergacheva L. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001